Australian Englishes and the Experiences of international students. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2007)
There is one salient feature that differentiates English from other Asian and European global languages. It is the way in which English has been subject to commodification and characterised as a marketable product (Habermas, 1990). In the context of a post-industrial society, English has assumed an important status as providing access to economic, educational and immigration opportunities (Singh, Kell and Pandian, 2002).